AN ELECTROCHEMICAL STUDY OF THE COBALT ELECTRODEPOSITION ONTO A CARBON FIBER ULTRAMICROELECTRODE - Mendoza-Huizar, Luis Humberto; Corona-Castro, Jair A.; Álvarez-Romero, Giaan A.; Rivera, Margarita; Rios-Reyes, Clara H.; Bañuelos-García, L.E.; García-Sánchez, E. (Journal of the Chilean Chemical Society, 2022)
A kinetic study of the cobalt electrodeposition onto carbon fiber ultramicroelectrodes of 11 µm of diameter from an aqueous solution containing CoCl2 0.01 M + NH4Cl 0.1 M was conducted at overpotential conditions. From the voltamperometric studies, it was found that the value of the diffusion coefficient is 1.2x10-5 cm2 s-1. The analysis of the current density transients indicates the existence of a 3D nucleation and growth process. Also, it was observed that the values of the number of active nucleation sites increases as the value of the applied potential decreases.